Online social media usage behavior of entrepreneurs in an emerging market: Reasons, expected benefits and intentions. Issue 2 (15th October 2018) - Turan, Mehmet; Kara, Ali
Abstract : Purpose: Online social media has become an important marketing communication tool for entrepreneurs and their customers because of its ability to simplify various constraints in the communication process. Online social media allows entrepreneurs to access customers, suppliers, partners and other necessary resources that were not easily reachable before at significantly lower costs. Therefore, the current study aims to examine entrepreneurs' motivations, expected benefits and intentions to use online social media in an emerging market. Design/methodology/approach: This study used a quantitative approach to investigate the entrepreneurs' online social media use behaviors. Data are collected from n = 368 entrepreneurial organizations using structured questionnaires and personal interviews. Confirmatory factor analysis (CFA) along with structural equation modeling (SEM) was used to test the hypothesized relationships in the conceptual model. Findings: Results from the data analyses show that entrepreneurs' perceptions about efforts needed, performance expectations and various social influences helped explain a significant proportion of the variation in entrepreneurs' intentions to use online social media. All hypotheses tested in the study were confirmed. Research limitations/implications: Efforts need to be spent on developing positive entrepreneurial attitudes toward online social media usage. As social media becomes more integrated with personal and business life, entrepreneurs need to use social networking sites to build relationships with existing customers or to reach new customers. A larger and more representative sample would have improved generalizability of the findings about entrepreneurial use of online social media. Future research studies should consider using additional independent measures to validate the study results. Practical implications: This study contributes to the entrepreneurial literature by providing empirical evidence for the link between entrepreneurs' perceptions and attitudes about social media and their intentions to use it in an emerging market. Additionally, entrepreneurs need to expend more effort in understanding and effectively using social media and should develop positive attitudes toward online social media. Entrepreneurs' feelings, perceptions and efforts need to be nurtured through support from online social media providers, educational institutions and local chapters of business organizations (i.e. SBA, Chamber of Commerce) alike. Originality/value: This research is one of the few studies that has attempted to examine the effects of various antecedent factors in the context of entrepreneurs' intentions to use online social media for business purposes in an emerging market. This study contributes to the entrepreneurial literature by providing empirical evidence for the link between entrepreneurs' perceptions and attitudes about social media and their intentions to use it in an emerging market. Additionally, this study contributes to our understanding about the role of social influences, effort and performance expectancies on the formation of entrepreneurial intentions to use social media.